Como o Oeste se perdeu: representação, nação e modernidade no Novo Western (1969-2012) - Borges, Rafael (2015)
This work starts from the questioning of changes perceived in filmic representations in film genre of the US Western, intending to offer an interpretation to them. Assuming that the Western deals with fundamental issues for the construction of the US nation's image - as the Manifest Destiny and the frontier thesis - it is proposed that these identified changes suggest reviewing and a desconstruction of the nation image elaborate by Americans themselves. However, in addition to the discussion about the deconstruction of this image, it is assumed the western as Eurocentric image, a myth that manifests in the United States the same myth of progress that legitimizes the Western modern project. Therefore, defends the thesis that the new cinematic representations that have gotten repercussion from the main prize of the US cinema over the years, indicate, ultimately, a critique of modernity itself, as discourse and historical process, allowing that glimpse a new time and a new project synthesized in idea of transmodernity.